2012
DOI: 10.3892/ijo.2012.1659
|View full text |Cite
|
Sign up to set email alerts
|

Novel dihydrobenzofuro[4,5-b][1,8]naphthyridin-6-one derivative, MHY-449, induces apoptosis and cell cycle arrest in HCT116 human colon cancer cells

Abstract: Colorectal cancer (CRC) is the second most frequent cancer in men and the third most common cancer in women in Korea. In spite of the significant advances in conventional therapeutic approaches to CRC, most patients ultimately die of their disease. There is a need to develop novel preventive approaches for this malignancy. This study was carried out to investigate the anticancer effect of the diastereoisomeric compounds, MHY-449 and MHY-450, novel dih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 33 publications
4
17
0
Order By: Relevance
“…Of note, the downregulation of caspases-3, -9, and -8, as well as cleavage of PARP, was observed in present study. The observed caspase-mediated properties of MHY-449 are in agreement with previous studies using colon (6) and prostate (7) cancer cells. We also demonstrated that MHY-449, in the presence of Z-VAD-FMK, prevented the degradation of PARP in these cells.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Of note, the downregulation of caspases-3, -9, and -8, as well as cleavage of PARP, was observed in present study. The observed caspase-mediated properties of MHY-449 are in agreement with previous studies using colon (6) and prostate (7) cancer cells. We also demonstrated that MHY-449, in the presence of Z-VAD-FMK, prevented the degradation of PARP in these cells.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we have determined that synthetic MHY-449 exerts potent antitumor effects in NSCLC cells. To the best of our knowledge, this is the first study describing this effect of MHY-449 on NSCLC cells, despite its documented cytotoxicity in numerous other cancer cell lines (5)(6)(7). MHY-449 can effectively induce NSCLC cells to undergo apoptosis.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…CRC is the fourth most common cancer in the world, but it is more common in developed countries. CRC is the third most common cancer and the fourth leading cause of cancer-related death in Korea and the incidence of CRC have been increased rapidly over the past few decades (1,2). While surgical resection cures >50% of CRC patients, 40-50% of these subjects eventually experience recurrences, leaving only a minority amenable to re-operation (3).…”
Section: Introductionmentioning
confidence: 99%